#Scanners 2 – The MOMENT: a new brain-controlled movie - Ramchurn, Richard; Wilson, Max L.; Martindale, Sarah; Benford, Steve (2018)
While many still consider interactive movies an unrealistic idea, current delivery platforms like Netflix, commercial VR, and the proliferation of wearable sensors mean that adaptive and responsive entertainment experiences are an immediate reality. Our prior work demonstrated a brain-responsive movie that showed different views of scenes depending on levels of attention and meditation produced by a commercialised home-entertainment brain sensor. Based on lessons learned, this demonstration exhibits the new interactions designed for our new brain-controlled movie, The MOMENT, being released in 2018.